Regenerative Limb Salvage: A Novel Technique for Soft Tissue Reconstruction of Pediatric Extremities - Saeg, Fouad; Chiccarelli, Elvira N.; Hilaire, Hugo St.; Lau, Frank H. (Journal of Reconstructive Microsurgery Open, 2020)
Background In complex extremity wounds, free flap-based limb salvage (fLS) is the standard of care. However, fLS is resource- and cost-intensive, and the limited availability of pediatric microsurgical expertise exacerbates these challenges. Regenerative LS (rLS) addresses these barriers to care. The aim of this study was to quantify the efficacy, safety, and cost-effectiveness of rLS in complex pediatric extremity wounds.Methods We conducted a retrospective cohort study of pediatric LS at a single hospital. Subjects were treated with fLS or rLS based on surgeon preference. Primary outcome measures were: definitive wound closure rates and time, rates of return to ambulation, number and length of procedures to achieve definitive closure, and rates of perioperative complications. Statistical analyses were performed utilizing the Wilcoxon Mann–Whitney U test with statistical significance set at p < 0.05.Results Over a 2-year period, nine consecutive patients presented with complex extremity wounds requiring fLS (n = 4) or rLS (n = 5). Demographics and wound characteristics were similar between groups. Compared with fLS, the rLS group achieved definitive wound closure 85.8% more quickly (13.8 vs. 97.5 days, p < 0.02), required 64.5% less operative time (132.6 vs. 373.0 minutes, p < 0.02), had fewer perioperative complications (0 vs. 5), and required fewer intensive care unit stays (0 vs. 1.3 days).Conclusion These data indicate that rLS is a safe and efficacious option in pediatric patients requiring soft tissue reconstruction for LS. Use of this novel technique can restore the reconstructive ladder, thereby expand patient access to pediatric LS while minimizing morbidity and reducing LS-related resource utilization.
Keywords: limb salvage; regenerative; pediatric; reconstruction; extremity; free flap